2005
DOI: 10.1073/pnas.0409344102
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Na+/K+-ATPase β1-subunit has a K+-dependent cell adhesion activity for β-GlcNAc-terminating glycans

Abstract: A 48-kDa ␤-N-acetylglucosamine (GlcNAc)-binding protein was isolated from mouse brain by GlcNAc-agarose column chromatography. The N-terminal amino acid residues showed the protein to be a mouse Na ؉ ͞K ؉ -ATPase ␤1-subunit. When the recombinant FLAG-␤1-subunit expressed in Sf-9 cells was applied to a GlcNAcagarose column, only the glycosylated 38-and 40-kDa proteins bound to the column. In the absence of KCl, little of the proteins bound to a GlcNAc-agarose column, but the 38-and 40-kDa proteins bound in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 34 publications
(26 reference statements)
1
25
0
Order By: Relevance
“…For GlcNAc-binding experiments, we adapted reported methods (Kitamura et al 2005). Two-hundred wild-type or homozygous Df(3R)CA3 embryos were selected at ∼16-20 h of development, frozen at −80°C, and ground in lysis buffer (PBS at pH 7.2, containing 1.54 mM K + , 1% igepal, 0.25 mM EGTA, 1× Roche Complete miniprotease inhibitor).…”
Section: Western Blot Analyses and Glcnac-binding Assaysmentioning
confidence: 99%
“…For GlcNAc-binding experiments, we adapted reported methods (Kitamura et al 2005). Two-hundred wild-type or homozygous Df(3R)CA3 embryos were selected at ∼16-20 h of development, frozen at −80°C, and ground in lysis buffer (PBS at pH 7.2, containing 1.54 mM K + , 1% igepal, 0.25 mM EGTA, 1× Roche Complete miniprotease inhibitor).…”
Section: Western Blot Analyses and Glcnac-binding Assaysmentioning
confidence: 99%
“…7 (26-31). [45][46][47][48][49][50] For the identification of binding domain within peroxisomal β-oxidation enzyme, a palmitoyl probe 31 was synthesized and examined in collaboration with Dr. Imanaka's group.…”
Section: )mentioning
confidence: 99%
“…NCX1 works in close partnership with Na,K-ATPase, by utilizing the sodium gradient generated by Na,K-ATPase to drive calcium efflux. Na,K-ATPase has also been shown to function as a motility and tumor suppressor (13,14) and is involved in the maintenance of epithelial polarity (15) and cell adhesion (16,17). Moreover, we previously reported that knockdown of Na,K-ATPase ␤ 1 -subunit (Na,K-␤) in MDCK cells led to mesenchymal phenotype accompanied by increased cell proliferation via activation of phosphoinositide-3 kinase (PI3K)/Akt and extracellular-signal-regulated kinase (ERK1/2) pathways (18).…”
mentioning
confidence: 99%